Empowerment of Youth in the Management of Natural Resources in Gintung Village, Sukadiri District, Tangerang Regency - Robi Kurniawan; Mila Azizah (International Research & Development for Human Beings (IRDH), 2025)
The management of productive and sustainable natural resources (SDA) is one of the keys to rural development. Gintung Village, Sukadiri District, Tangerang Regency has great potential in agriculture, fisheries, and ecotourism, yet it has not been fully utilized. This research aims to empower the youth to take an active role as a driving force in managing SDA based on innovation and sustainability. The implementation methods include situational analysis, technical training, entrepreneurial mentoring, marketing digitization, and continuous evaluation. The results of the activities show a significant increase in the knowledge, skills, and motivation of the youth in managing SDA potential. Several youth groups have successfully initiated organic farming ventures, catfish farming, and the promotion of local products through digital media. This program also encourages the creation of environmental awareness and multi-stakeholder collaboration among youth, village governments, academics, and the private sector. This success proves that a participatory approach, targeted training, and sustainable support can strengthen the capacity of youth in promoting self-sufficient, competitive, and sustainable village development.